European Regional Conflicts of the Second Half of the 1930s and the Evolution of the National-Socialist Image of Enemy - Malay, Vera V.; Krupskaya, Svetlana U.; Orehova, Marina S.; Timoshkova, Olga A.; Fomichev, Nickolay N. (Journal of History Culture and Art Research, 2018)
Regional conflicts in West and Central Europe, in the second half of the 1930s symbolized the collapse of the Versailles system, polarizing the situation and affecting the balance of power on the continent. All of them had international aspects, including propaganda aspect. European regional conflicts (1936-1939) have become a convenient case for approbation of the "old" Nazi ideological postulates as well as for development of "new" ones. The result of such propaganda work was the formation of an "enemy image", actively used in the future on the fronts of World War II. The article deals with the design and implementation by the Nazis in the German and European environment proper of the image of an "external" enemy, on example of the introduction of Hitler troops into the Rhine zone (1936), the Spanish Civil War (1936-1939), the Anschluss of Austria (1938) and Munich conference (1938).